Kestrel nest box occupancy and fledging rates and the effect of kestrel presence and absence on bird abundance and activity in fruiting crops in the Niagara Region and Norfolk County. (January 2021) - Jasinski, Mary; Hughes, Margaret; Fraser, Hugh W.; Fitzgerald, Susan; Willwerth, James J.
Abstract: Frugivory by birds has been well documented and can have significant economic impacts globally. Invasive or pest species such as European starlings ( Sturnus vulgaris ) and American robins ( Turdus migratorius ) have been most frequently implicated and are omnivorous, adaptable, and opportunistic. Reducing their impact on ripening fruit crops is a constant topic of research in crop protection. Often, deterrents are installed at time of ripening but are unsuccessful if overused, as their continued presence at a single location allows for habituation by frugivorous species. American kestrels ( Falco sparverius ) are currently in decline in Southern Ontario. Habitat fragmentation, urbanization, climate change and invasive species have all contributed to this phenomenon. Kestrels, being cavity nesting birds, can be attracted to nest or roost in areas by installing kestrel nest boxes. Although not present during the ripening period of the fruiting crops studied, kestrels significantly reduced overall bird activity and abundance, and the abundance of thrush species (American robins) during their use of nest boxes in sensitive crops in the Niagara Region, while also promoting the continued presence of an at-risk species. Facilitating the presence of kestrels using nest boxes, or promoting the presence of birds of prey in general, can therefore be an effective bird deterrent mechanism. However, competition for the use of nest boxes from invasive species such European starlings decreased the successful occupancy rate of installed nest boxes by either kestrels or other beneficial species. Therefore, the monitoring, management, and maintenance of installed boxes is integral to their success as a deterrent mechanism and should be considered before their installation. Highlights: The presence of the American Kestrel significantly impacted the presence and activity of birds in crop fields. Kestrel boxes which had been occupied in one breeding season were more likely to be occupied the following year. Use of nest boxes can encourage the nesting of other beneficial species, promoting the use of nest boxes in a larger context. Invasive species decreased the successful occupancy rate of installed nest boxes.